Application of GIS-Base GALDIT for vulnerability assessment to saltwater intrusion of Holocene coastal aquifer: a case of Quang Nam - Da Nang city, Vietnam - Long, Phan Nam; Dat, Huynh Tien (Vietnam Journal of Earth Sciences, 2020)
Groundwater is an essential resource which is influenced by salt water due to the groundwater exploitation in Holocene aquifer of Quang Nam - Da Nang. Hence, the measures for preventing saltwater intrusion and better groundwater management are required. In this study, GALDIT method was utilized to identify the salt water intrusion (SWI) vulnerability zones using monitoring data in Holocene aquifer of Quang Nam - Da Nang. The results of GALDIT method indicated that Da Nang and Hoi An cities were in the high SWI vulnerability zones. The moderate SWI zones were dominant and low vulnerability zones were at the southern part of the study area. The analysis of the monitoring data showed the occurrence of SWI far inland, up to the distance of 12.5 km from the sea shore and suggested the impact of human activities on SWI. The analysis of monitoring data together with GALDIT index indicated that the important of the groundwater abstraction depth or the occurrence of fresh-salt groundwater interface should be considered to improve the result of GALDIT method for the prevention of SWI. In short, the GALDIT used in this study is an important approach for the prevention of SWI in the study area.